"Gaydar": The Perception of Sexual Orientation From Subtle Cues. (December 2016) - Rule, Nicholas O.; Alaei, Ravin
Though many of people's impressions about each other stem from qualities that are obvious or apparent, social perceptions also rely on a variety of subtle cues that guide judgment and behavior. For example, emerging work has increasingly elucidated the conditions and means by which individuals' accuracy in judging others' sexual orientation is better than chance. We discuss these here, focusing on four domains from which people draw cues to accurately perceive sexual orientation: how people adorn themselves (adornment), how they move (actions), how they sound (acoustics), and how they look (appearance). Moreover, we describe how certain factors, such as one's own sexual orientation, can constrain or facilitate this accuracy and describe the various negative social and occupational consequences that may result from cues that someone is gay or straight.